A Sleeping Giant - A Case Report of Echinococcosis - Silva, Madalena Sousa; Carneiro, António; Silva, Isa; Pereira, Luís Miguel; Fernandes, Natália (Archives of Clinical and Medical Case Reports, 2020)
Echinococcosis is a parasitary disease produced by Echinococcus spp. It is endemic in some European regions such as Portugal. We present the case of a patient who was admitted for de-novo ascites. In the course of the investigation, a bulky hepatic hydatid cyst was diagnosed. The cyst was in the inactive phase of the disease, calcified and it bore no symptoms. The ascites was due to heart failure and resolved with appropriate treatment. The relevance of the case relates to the exuberance of the cyst and the interesting images obtained.